Penerapan Video Pembelajaran Berbasis Kearifan Lokal dalam Meningkatkan Kompetensi Guru Sosiologi di SMA Negeri 1 Seram Bagian Barat - Merti Seska Rosely; Yandri Tuarissa; Nurwati Tamrin (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
This study aims to examine the meaning contained in the Cakalele dance ritual as a local wisdom of the Maluku tribe that can be used as a source for sociology learning at the high school level or equivalent. Sociology, as a social science, can utilize this local wisdom to enrich understanding and help students understand sociology learning themes. This study used descriptive qualitative research. Data collection was conducted through non-participant observation, in-depth interviews, and documentation. Data analysis used interactive techniques. The results of the study can be conveyed that learning management in the local wisdom of the "Cakalele dance" can be used as a source of sociology learning because it is relevant to one of the sociology learning themes in grade X in the independent curriculum, namely social phenomena in a multicultural society. In addition, utilizing the Cakalele dance ritual as a learning resource is a contextual approach that can help students understand one of the sociology learning topics because they can observe events directly in real life. By utilizing the local wisdom of the Cakalele dance as a learning resource, it can create creative, innovative, and enjoyable sociology learning.